ROLE OF THE INDONESIAN NAVY TASK UNIT TO SUPPORTING TECHNOLOGY TRANSFER OF SUBMARINE BY DSME SOUTH KOREA-PT PAL INDONESIA - Nurcahya Dwi Asmoro; Udisubakti Ciptomulyono; I Nengah Putra; Ahmadi Ahmadi; Okol S Suharyo (JOURNAL ASRO, 2018)
ABSTRACT Indonesian Navy has a strategic project of building three units of submarines in collaboration with DSME South Korea. In the development cooperation submarine contract DSME also include the implementation of Technology Transfer (TT) between South Korea DSME with PT.PAL Indonesia. Therefore necessary strategies to get success TT process submarines. The task force Navy submarine construction that has always worked between DSME and PT.PAL has helped realize the moral burden for the technology transfer program. How Submarine Task Force strategy to ensure the success of PT.PAL accept TT of DSME? SWOT analysis tries to analyze the variables that influence the strategy and product that work discipline, facilities and infrastructure, the relationship between team performance and PT.PAL DSME is a variable that must be maintained and improved. Submarine task force as a motivator can act as a driving force in improving the performance and things - other matters relating to the development of technology over the course of the submarine. Keywords: Submarine, TOT, SWOT